Central Bank COVID-19 Policy and Equities Market Sensitivity in Europe and the U.S. - Hütteroth, Alexander (International Journal of Applied Research in Management and Economics, 2023)
With the beginning of the COVID-19 pandemic, the Federal Reserve (Fed) as well as the European Central Bank (ECB) have pursued a very expansionary monetary policy to mitigate potential economic impacts. In 2022, inflation fears caused bond yields to rise significantly, and the prevailing academic view is that this environment has a negative impact on stock market performance and high-growth stocks in particular. In this paper the performance of stock markets STOXX Europe 600 and S&P 500 is analysed in relation to the central bank policy from 2020 to 2022. The assumption is that the outperformance of single sectors was due to interest rates and a mean-reversion process will occur in 2022. The results of the paper show no significant correlation between interest rates and sector outperformance but between both indices. On this basis, further research on individual sectors, stocks, and other possible variables such as inflation is recommended.